2016
DOI: 10.1111/eva.12431
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating virulence factor availability can have complex consequences for infections

Abstract: Given the rise of bacterial resistance against antibiotics, we urgently need alternative strategies to fight infections. Some propose we should disarm rather than kill bacteria, through targeted disruption of their virulence factors. It is assumed that this approach (i) induces weak selection for resistance because it should only minimally impact bacterial fitness, and (ii) is specific, only interfering with the virulence factor in question. Given that pathogenicity emerges from complex interactions between pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The link between pyoverdine and virulence has been clearly established in many contexts, including in C. elegans Liquid Killing and in murine infections. However, recent studies in a Galleria mellonella infection model demonstrated a more complicated relationship between pyoverdine and pathogenesis (Weigert et al, 2017). The addition of exogenous pyoverdine at low concentrations seemed to attenuate pathogen virulence.…”
Section: Discussionmentioning
confidence: 99%
“…The link between pyoverdine and virulence has been clearly established in many contexts, including in C. elegans Liquid Killing and in murine infections. However, recent studies in a Galleria mellonella infection model demonstrated a more complicated relationship between pyoverdine and pathogenesis (Weigert et al, 2017). The addition of exogenous pyoverdine at low concentrations seemed to attenuate pathogen virulence.…”
Section: Discussionmentioning
confidence: 99%
“…This is easily measured when virulence and growth are correlated and when symbionts can be distinguished in a multiple infection 8 . However, virulence is not always related to symbiont growth, as assumed by most theoretical models, but might be due to immunopathology 73 , 74 . In such cases, symbionts in a multiple infection with facilitation might interact in such a way that virulence does not correspond to the sum of the virulence measured in each single infection.…”
Section: Ecological and Evolutionary Consequences Of Facilitationmentioning
confidence: 99%
“…This positive feedback, triggered by successful iron uptake, is opposed by a negative feedback operated by Fur (ferric uptake regulator), which silences pyoverdine synthesis once enough iron has been taken up (16,44). Our results can be interpreted in the light of these feedbacks, given that the relative strength of the opposing feedbacks determines the resulting pyoverdine investment levels (45). For example, producer micro-colonies reach higher cell densities in mono-compared to mixed cultures (figure 3, after 3h: 13.2 ± 2.3 versus 6.7 ± 1.3 cells; after 5h: 122.7 ± 17.9 versus 55.0 ± 8.1 cells, respectively).…”
Section: Discussionmentioning
confidence: 80%